Oligocene fossil oak woods, Quercoxylon lecointrei GAZEAU & KOENIGUER, decayed by a pocket-rot fungus (PALAEONTOGRAPHICA ABTEILUNG B-PALAOPHYTOLOGIE, 2012)
Silicified fossil woods were collected from an alluvial deposit in theAllier valley, Massif Central, France. These woods, dated as Oligocene, are identified as Quercoxylon lecointrei GAZEAU & KOENIGUER, a fossil species close to the extant Mediterranean holm oak (Quercus ilex L.). The specimens studied show numerous individual cavities, each 0.5-1.3 x 0.2-0.5 cm in size, but these generally do not affect multiseriate rays. Despite the lack of fungal remains, the decay pattern is comparable in appearance with that of present-day pocket-rot caused by Basidiomycetes, and particularly by Xylobolus frustulatus (PERS.: FR.) BOIDIN. Indications of possible host response to fungal attack include abundant tyloses in vessels and dark substances filling the cells.
The following values have no corresponding Zotero field: pub-location: NAEGELE U OBERMILLER, SCIENCE PUBLISHERS, JOHANNESSTRASSE 3A, D 70176 STUTTGART, GERMANY publisher: E SCHWEIZERBARTSCHE VERLAGS